TATA RUANG RUMAH TRADISIONAL DI KECAMATAN BANYUBIRU, KABUPATEN SEMARANG - Wahyudi, Agung; Wibawa, Baju Arie (Jurnal Teknik Sipil dan Arsitektur, 2025)
Banyubiru is one of the sub-districts in Semarang Regency which is located on the slopes of Mount Telomoyo. Traditional houses in this area especially in Sepakung village and its surroundings, are javanese houses with distinctive characteristics that are different from Javanese houses in other areas, namely a single mass with two or three roof forms extending to back. Inside the house there are still four sakaguru pillars under the main roof. This study aims to reveal the shape of the houses in Sepakung village and its surroundings. We will look at the spatial pattern of the house, to study the extent to which the Javanese house layout pattern is still being applied or not. The method used is descriptive-analytical, which is looking at existing phenomena and then analyzing them by comparing them with the original Javanese house layout. From the observations made, the shape of the traditional house around the village of Sepakung still shows a relationship with the form of a traditional Javanese house (joglo), only the shape is simplified into one mass. The spatial pattern itself shows differences from the original Javanese house layout due to its simplification, such as the phenomenon of senthong Tengah desacralization, positional shift and addition of senthong/bedroom as needed. Despite these differences, there are still characteristics of Javanese spatial planning that are still maintained, namely the construction of the saka guru with its rong-rongan.